THE EFFECT OF PREPARATION METHODS OF GREEN FIG CUTTINGS ON THEIR ROOTING - Dilafruz Shamilovna, Nurmukhamedova (American Journal of Botany and Bioengineering, 2025)
In the article shown that, the position of the fig cutting on the shoot (degree of maturity) plays a decisive role in its ability to root. Green cuttings taken from the middle and lower parts of the shoot show a high rooting rate of up to 93–97%.